Pengaruh Inflation Rate Dan Suku Bunga Terhadap Perkembangan Impor di Indonesia : Studi Kasus Pada Masa Transisi Covid-19 Tahun 2021-2022 - Mufti Ali; Rosid Kurniawan; Cep Jandi Anwar; Indra Suhendra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research iiis motivated by phenomena based on previous phenomena and research gaps based on research that has been goinggg on for aaa long time. Therefore, it iiis necessary to carry out further research tooo test the consistency of the results and the results of previous studies. also to review existing research gaps in the research topic. The focus of research iiin writing this thesisss is how inflation and interest ratesss significantly influence the development of imports in Indonesia, how inflationnn and interest rates significantly affect the development of imports in Indonesia, and how much influence inflation and interesttt rates have on development. imports iiin Indonesia. The dataaa used in this researchhh is secondaryyy data. Secondary dataaa iiis research information obtained (obtained and stored by other parties) indirectly through the media. Secondary data for thisss study were taken from annual reports published by Bank Indonesia. and the annual report of Statistics Finland. The investigation strategy utilized in this think about is different relapse examination. The reason of this relapse investigation is to urge a comprehensive picture of the relationship between the free and subordinate factors of each company's performance. Before running multiple linear tests, this method requires a classic hypothesis test to get the best results. SPSS software version 23 is used for data processing